Erythropoietin Increases Myelination in Oligodendrocytes: Gene Expression Profiling Reveals Early Induction of Genes Involved in Lipid Transport and Metabolism - Gyetvai, Georgina; Hughes, Trisha; Wedmore, Florence; Roe, Cieron; Heikal, Lamia; Ghezzi, Pietro; Mengozzi, Manuela (Frontiers in Immunology, 2017)
Several studies have shown that erythropoietin (EPO) has neuroprotective or neuroreparative actions on diseases of the nervous system and that improves oligodendrocyte (OL) differentiation and myelination in vivo and in vitro. This study aims at investigating the early molecular mechanisms for the pro-myelinating action of EPO at the gene expression level. For this purpose, we used a differentiating OL precursor cell line, rat central glia-4 cells. Cells were differentiated or not, and then treated with EPO for 1 or 20 h. RNA was extracted and changes in the gene expression profile were assessed using microarray analysis. Experiments were performed in biological replicates of n = 4. Differentiation alone changed the expression of 11% of transcripts (2,663 out of 24,272), representing 2,436 genes, half of which were upregulated and half downregulated. At 20 h of treatment, EPO significantly affected the expression of 99 genes that were already regulated by differentiation and of 150 genes that were not influenced by differentiation alone. Analysis of the transcripts most upregulated by EPO identified several genes involved in lipid transport (e.g., Cd36) and lipid metabolism (Ppargc1a/Pgc1alpha, Lpin1, Pnlip, Lpin2, Ppard, Plin2) along with Igf1 and Igf2, growth factors known for their pro-myelinating action. All these genes were only induced by EPO and not by differentiation alone, except for Pnlip which was highly induced by differentiation and augmented by EPO. Results were validated by quantitative PCR. These findings suggest that EPO might increase remyelination by inducing insulin-like growth factors and increasing lipid metabolism.